A Study on a Solar Simulator for Dye Sensitized Solar Cells - Kyoung-Jun Lee; Jeong-Hoon Kim; Ho-Sung Kim; Dongsul Shin; Dong-Wook Yoo; Hee-Je Kim (International Journal of Photoenergy)
Dye-sensitized solar cells (DSSC) are emerging low-cost, simple alternatives to conventional solar cells. While there has been considerable study on improving the efficiency of DSSCs, there has not been sufficient research on a photovoltaic power conditioning system adaptable to DSSCs or on a solar simulator for DSSCs. When DSSCs are commercialized in the near future, the DSSC modules must be connected to an adaptable power conditioning system in order to manage the energy produced and provide a suitable interface to the load. In the process of developing a power conditioning system, a solar simulator with the characteristics of DSSCs is essential to show the performance of the maximum power point tracking. In this paper, a virtual DSSC is designed and simulated in PSIM. Irradiation factors, temperature and shadow effects are considered in dynamic link library block in PSIM which is linked to the external C routine. A 100 W converter is built to show the performance of a DSSC as the solar simulator controlled by a digital signal processor.